Ulama, Bureaucrats, and Legislators: Political Negotiations in the Making of Marriage Law No. 1 Of 1974: Ulama, Birokrat, dan Legislator: Negosiasi Politik dalam Pembuatan Undang-Undang Perkawinan No 1 Tahun 1974 - Farid, Miftah; Taufan, Rudi; Pratama, Riki (Dame Journal of Law, 2026)
Law No. 1 of 1974 on Marriage marks a pivotal turning point in the formation of modern family law in Indonesia. While existing scholarship largely focuses on the statute’s normative content and social consequences, limited attention has been given to the political processes through which the law was produced. This article reconstructs the making of the 1974 Marriage Law as a negotiated political settlement among Islamic scholars (ulama), state bureaucrats, and legislators. Adopting a historical socio-legal approach, the study draws on ministerial archives, parliamentary records, policy documents, and contemporary media sources from 1967–1974, analyzed through process tracing to identify the causal mechanisms shaping legal outcomes. The findings demonstrate that the legislation evolved through four phases technocratic drafting, parliamentary contestation, informal elite lobbying, and final compromise during which competing moral, administrative, and political authorities constrained and accommodated one another. The resulting statute embodies a hybrid structure that recognizes religious legitimacy while placing family practices under state administrative control. The article proposes a triangular negotiation model to explain law-making as a multi-actor process and contributes to debates on moral regulation and managed legal pluralism in Muslim-majority societies.